2016
DOI: 10.1080/10439463.2016.1262364
|View full text |Cite
|
Sign up to set email alerts
|

Is crime analysis at the heart of policing practice? A case study

Abstract: Following the introduction of National Intelligence Model (NIM) in 2004, this paper explores whether crime analysis has been integrated into policing practice. Fieldwork was conducted in one UK police force with both analysts and police officers. Findings from the analysis of semistructured interviews and focus group discussions suggest that while crime analysis is acknowledged as being central to the business of everyday policing, police officers' general lack of understanding of how analysts work and their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 27 publications
1
34
0
1
Order By: Relevance
“…For example, whilst hypothesis testing was shown by Chainey (2012) to improve analysis, this was an approach used infrequently by many analysts. Further, this and other research (Belur and Johnson, 2016;Townsley, et al, 2011;Sissens, 2008) found analysts key skills are hampered by poor training, particularly in the application of rigorous scientific research methods. Innes et al (2005) found that police analysts did not use rigorous methodologies in developing objective analytical conclusions.…”
Section: The Demise Of the Police Analystmentioning
confidence: 72%
See 4 more Smart Citations
“…For example, whilst hypothesis testing was shown by Chainey (2012) to improve analysis, this was an approach used infrequently by many analysts. Further, this and other research (Belur and Johnson, 2016;Townsley, et al, 2011;Sissens, 2008) found analysts key skills are hampered by poor training, particularly in the application of rigorous scientific research methods. Innes et al (2005) found that police analysts did not use rigorous methodologies in developing objective analytical conclusions.…”
Section: The Demise Of the Police Analystmentioning
confidence: 72%
“…Innes et al (2005) found that police analysts did not use rigorous methodologies in developing objective analytical conclusions. In essence, seventeen years after the implementation of the NIM, research in both the UK (Belur & Johnson, 2016) and the USA (Carter, 2015;Santos & Taylor, 2014) questions whether police analysts are able to think analytically. This is quite surprising as Santos (2014) demonstrates that crime analysis is an essential component in directing a variety of policing activity.…”
Section: The Demise Of the Police Analystmentioning
confidence: 99%
See 3 more Smart Citations